Aku Suka Makan Sehat: Pengenalan Gizi Seimbang Melalui Cerita dan Permainan pada siswa TK A - Lahay, Sitty Fadhilla Fitrianty; mulyadi, jesica -; Anita, Astri - (Universitas Negeri Gorontalo, 2025)
Providing knowledge about nutritious food to young children is an essential step in shaping healthy eating habits and supporting their optimal growth and development. This community service activity aimed to enhance the understanding of students at TK A Aisyiyah Bustanul Athfal Bolihuangga, Gorontalo Regency, regarding the principles of balanced nutrition through engaging learning methods appropriate to their developmental stage. The program was implemented on October 14, 2025, involving 17 students, and utilized several approaches, including material delivery, educational video presentations, and interactive games that required students to sort nutritious and non-nutritious foods. The results showed that children became more capable of identifying healthy food types, actively participated in all activities, and demonstrated improved comprehension through visual and motor-based tasks. The learning-through-play approach proved effective in increasing students’ enthusiasm and fostering positive behaviors related to food choices. Overall, this activity provided an enjoyable and meaningful nutrition education experience that has the potential to support children’s health and learning abilities in the future.